Plagued to Death by Ableism: What the COVID-19 Pandemic and the Expansion of Eligibility for MAID Reveal About the Lethal Dangers of Medical and Systemic Ableism in Canada - Janz, Heidi (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
In this paper, I draw on my research and experience as a disability ethics educator and advocate in order to demonstrate that both Canada’s COVID-19 response and its expansion of eligibility for MAID are symptoms of the medical and systemic ableism that afflicts Canadian society. I conclude with a consideration of the enduring danger that eugenic ableism disguised as autonomy poses for people with disabilities in a Canada where COVID-19 may be waning, but where the contagion of ableism turned lethal through MAID continues to spread.